Performance evaluation of OFDM and MC-CDMA based cognitive radio system - Salem Bindhaiq, Salem Mohammed (2012)
The present development of high data rate wireless applications has lead to extra bandwidth demand. However, finding a new spectrum bandwidth to accommodate these applications and services is a challenging task due to lack of spectrum resources. In fact, recent studies have shown that the spectrum are utilized inefficiently especially for conventional spectrum allocation. Therefore, in order to enhance spectrum efficiency, Federal Communications Commission (FCC) has proposed dynamic spectrum access (DSA) mechanism, where unlicensed users can opportunistically borrow unused spectrum from licensed owners. The radio that enables this concept is called Cognitive Radio (CR). Nevertheless, it is difficult for single transmission to get a large contiguous frequency spectrum block in DSA and this have significant impact on broadband and multi-carrier transmission systems such as Orthogonal Frequency Division Multiplexing (OFDM) and Multi-carrier Code Division Multiple Access (MC- CDMA). This thesis investigates on non-contiguous OFDM (NC-OFDM) and non-contiguous MC-CDMA (NC-MC-CDMA) system. The implementation of NC-OFDM and NC-MC-CDMA systems provide high data rate via large number of non-contiguous sub-carriers without interfering to the existing transmissions by turning off the sub-carriers corresponding to these spectrum bands. This thesis evaluates Bit Error Rate (BER) performance of NC-OFDM and NC-MC-CDMA on mobile scenario where each propagation path will experience an apparent shift in frequency due to the relative motion between the transmitter and receiver while the number null sub-carriers is constant for all.